Prevalence of Healed Plaque and Factors Influencing Its Characteristics Under Optical Coherence Tomography in Patients With Coronary Artery Disease: A Systematic Review, Meta-Analysis, and Meta-Regression - Feng, Xunxun; Liu, Yang; Yang, Jiaqi; Zhai, Guangyao; Zhou, Yujie; Guo, Qianyun (Frontiers in Cardiovascular Medicine, 2021)
Aim: The purpose of this study was to determine the prevalence of healed plaque and its characteristics under optical coherence tomography (OCT) through a formal systematic review, meta-analysis, and meta-regression. Methods and Results: Thirteen studies were selected from MEDLINE, EMBASE, Cochrane, and online databases. The overall incidence of healed plaques was 40% (95% CI: 39–42), with 37% (95% CI: 35–39) in patients with acute coronary syndrome (ACS) and with 46% (95% CI: 43–49) in patients with stable angina pectoris (SAP). The incidence of healed plaque among culprit plaques (48%, 95% CI: 46–50) was nearly two times higher than that among non-culprit plaques (24%, 95% CI: 21–27). The incidence of thin cap fibroatheroma (TCFA), plaque rupture, microvessel, macrophage accumulation, and calcification was significantly higher in the healed plaque group. Meta-regression revealed an association between smoking (P = 0.033) and healed plaque rupture. Gender (P = 0.047) was independently associated with macrophage accumulation, and mean low-density lipoprotein cholesterol (LDL-C) was independently associated with microvessel. Conclusions: In summary, with a total incidence of 40%, the incidence of healed plaques under OCT was higher in SAP than in ACS, and higher in culprit plaques than in non-culprit plaques. Higher incidence of TCFA, plaque rupture, microvessel, macrophage accumulation, and calcification was found in the healed-plaque group. Smoking, gender, and mean LDL-C level were associated with healed-plaque characteristics.